Fourth Industrial Revolution Tools to Enhance the Growth and Development of Teaching and Learning in Higher Education Institutions: A Systematic Literature Review in South Africa - Lilian Ifunanya Nwosu; Makuena Clementina Bereng; Tlotlo Segotso; Ngozi Blessing Enebe (Research in Social Sciences and Technology- OpenED Network, 2023)
The Fourth Industrial Revolution (4IR) has been the subject of discussion, and in most cases, it has been seen as a danger to jobs and conventional methods of doing things. Concerns over the preparation of the South African educational systems for 4IR have been raised as a result. Many industries still lack advanced understanding of 4IR, but the concept is already gaining ground in a variety of economic areas. As a result, academics, business professionals, and legislators are paying closer attention to 4IR. The researchers were inspired to look at how 4IR techniques were applied in South African higher education institutions to advance the growth and development of teaching and learning by this obvious knowledge gap. To investigate how 4IR technologies improve the growth and development of teaching and learning in South African higher education institutions, this study used a systematic literature review (SLR) methodology. A search procedure, research key words, inclusion and exclusion criteria, and quality assessments of chosen literature were used in conjunction with the SLR approach. This study found that some South African higher education institutions have successfully adopted 4IR technologies for virtual and contact instruction. The research further saw that academics and support staff utilised various 4IR tools. This is done through a virtual or hybrid classroom, artificial intelligence, and the internet of things, with different devices to send students messages, schedule Zoom classes, and provide feedback and educational resources. However, the study made some recommendations that academics can use to make sure that 4IR is effectively integrated to support the expansion and improvement of teaching and learning in higher education institutions. Future research directions were suggested, and the study came to the conclusion that South Africa could change the direction of the management of the education sector by implementing various 4IR tools in higher education institutions.